The effects of initial microstructure on the creep property of a 4th generation single crystal superalloy at mediate temperature and high stress - Huanchang Duan; Yuan Cheng; Xinbao Zhao; Lijie Qiao; Wanshun Xia; Quanzhao Yue; Jiachen Xu; Yuefeng Gu; Ze Zhang (Journal of Materials Research and Technology)
The creep properties at 800 °C and 735 MPa were examined in Ni-based single crystal superalloys (SCs) with different microstructure characteristics to systematically investigate the effects of initial microstructure on the creep property at mediate temperature and high stress. The creep life decreased monotonically with the increasing primary aging temperature, which increased both the γ channel width and size of γ′ phase. The creep resistance was mainly determined by the γ channel width and stacking fault energy in γ′ phase. Narrow γ channels and low stacking fault energy in γ′ phase enhanced the creep resistance. Additionally, the fine γ′ particles embedded within the γ channel when aging at higher temperatures could not improve the creep performance significantly. The results provided a reference for the design of heat treatment procedure.